Adaptation of The Diabetes Distress Scale on a Russian-speaking sample of patients with type 1 and type 2 diabetes mellitus - N. V. Likhodey; V. E. Epishin; M. F. Kalashnikova; A. M. Kaurova; M. V. Tulupova; Y. P. Sych; I. B. Bondareva (Сахарный диабет)
BACKGROUND: Diabetes distress (DD) is the negative emotional or affective experience resulting from living with diabetes. DD is a negative predictor of blood glucose control and quality of life, and may lead to decreased adherence to treatment. To diagnose DD, questionnaires are used to screen the emotional state and psychosocial aspects. In the study, linguistic, cultural adaptation and assessment of the psychometric properties of the Russian version of the questionnaire “The Diabetes Distress Scale” were conducted among patients suffering from T1DM and T2DM.Patients with diabetes mellitus (DM) have diabetic distress as one of the most common mental disorders along with depression. Depression and diabetic distress increase the risk of death in diabetes, negatively affect treatment adherence and self-monitoring of glycemia. Identification of these conditions among patients with T1DM and T2DM can contribute to their timely correction.AIM: To carry out linguistic and cultural adaptation of the questionnaire “The Diabetes Distress Scale” and evaluate the psychometric properties of the Russian version of the DDS questionnaire on a Russian-speaking sample of patients with T1DM and T2DM.MATERIALS AND METHODS: A study was conducted on a sample of 198 patients with T1DM and T2DM; data was collected on the use of the Russian version was collected DDS scales, as well as the EQ-5D-5L (European Quality of Life Questionnaire), SPANE (Positive and Negative Experiences Scale) and HADS (Hospital Anxiety and Depression Scale) scales. The last three scales were used to assess the convergent validity of the adapted questionnaire. Reliability of the DDS questionnaire was assessed using Cronbach’s α coefficient of internal consistency and participant retest after 1–4 months.RESULTS: The factor structure of The Diabetes Distress Scale questionnaire is fully reproduced when all 17 questions are included (measurement model fit indicators: CFI=0.981, RMSEA=0.055, TLI=0.967). The internal consistency of the subscales (α ϵ [0.836; 0.874]) and the questionnaire as a whole (α=0.948) is assessed as high. Significant correlations of the adapted methodology and its subscales with the scales of the EQ-5D-5L, SPANE, HADS questionnaires were obtained, the closest connections (Rho ϵ [0.370; 0.437], p<0.01), which indicates good external validity of the adapted methodology.CONCLUSION: The Russian version of the DDS questionnaire has good psychometric properties. It is a valid and reliable tool for assessing diabetes distress among patients with T1DM and T2DM and can be recommended for use in clinical practice for timely diagnosing depression and DD.